Measurements and Analysis of Mobile Satellite Signal Performance Using Handheld GPS Receiver - Kismet, Hong Ping; Ibrahim, Abba; Wan Azlan, Wan Zainal Abidin; Thelaha, Hj Masri (2012)
There is need for experimental data in the less developed and developing countries such as Africa, Asia and Latin America for the study and analysis of mobile satellite signal performance for communication purposes. The experiments were carried out in open space area with no obstruction of the direct wave. Comparisons were made between the soft reformatted data obtained in Kano, Kota Samarahan in Sarawak and Fukuoka in Japan. Data acquisition system developments were designed to manage the open space environment satellite propagation data for the less develop regions, whereby adaptive graphical user interface (AGUI) was designed and developed to records the propagations data. Therefore the recorded data will be used to evaluate the signal performance in term of SNR, azimuth angles and satellite elevation angles. Results obtained from analysis will be used to determine the characteristics of the open space environment. This method can be used to encourage more experimental works in the less develop countries. The analysis produced an important part in the studies of the signal performance. The hyper-terminal intercepts and adaptive graphic user interface were used to evaluate the previous data acquisition system conducted in Fukuoka and Stuttgart. The analysis for ionospheric effect on Mobile Satellite (MS) was conducted by comparing data obtained in Kota Samarahan, Kano with the data obtained in Fukuoka Japan. The experimental work was conducted with reduced cost and simple equipments so as to encourage more experimental studies on MS signal performance. Future research studies can be done by designing a program that will link and monitor the pilot data acquisition system placed in remote areas. Rain sensor and satellite display view can be added to the AGUI.